Peningkatan Pemahaman Konsep Dengan Pendekatan Reciprocal Teaching di SMP N 2 Kartasura - Kusumaningrum, Nur Hasanah Dwi, Drs. Ariyanto, M.Pd (2016)
The aim of this research is to improve the understanding of mathematical concepts in SMP N 2 Kartasura with Reciprocal Teaching uses the same approach. This research is a classroom action research conducted collaboratively between researchers and teachers of mathematics.Recipients action is class VIIIF SMP N 2 Kartasura as many as 30 students and the perpetrator is a teacher of mathematics.Data collection techniques in this study using observation, testing, field notes, and documentation.Data analysis techniques used in this study is the reduction, data presentation, and conclusion. The results showed an increased understanding of the concept of visits of1) the ability to restate a concept of an act of prior actions 9 students (30%) after the action rose to 20 students (66.67%) and the ability to apply the concept of a prior act of 10 students (33.33%) after the action increased to 23 students (76.67%) Based on the description The above concluded that this approach can improve the Reciprocal Teaching math problem solving.